Power ultrasound assisted mixing effects on bread physical properties - Che Pa, Nasrul Fikry; Chin, Nyuk Ling; Yusof, Yus Aniza; Ab. Aziz, Norashikin (Elsevier, 2014)
Power ultrasound was applied during in-situ bread dough mixing process at power level of 1.00, 1.50, 2.05 and 2.50 kW for time durations of 10, 20, 30 and 40 min. Well mixed doughs were subjected to standard proofing and baking processes where physical properties of bread like mass, volume and density were investigated. Power ultrasound significantly (P < 0.05) altered the physical properties of bread with bread volume increase by 19%, while bread mass and density reduced by 2.1% and 17%, respectively at maximum ultrasound power of 2.50 kW for exposure of 40 min.